Pancreatic collision tumour: mucinous cystadenoma and renal clear cell carcinoma metastasis. - Morzoletto Pedrollo, Ivan; Henz Concatto, Natália; dos Santos Machado, Simone Márcia; Bersch Osvaldt, Alessandro; Lorenzoni Almeida Ghezzi, Caroline (Clinical and Biomedical Research, 2021)
We present a clinical, radiological, surgical and anatomopathological correlation case of a 49-year-old female with a prior nephrectomy due to a clear cell renal cell carcinoma (RCC), who discovered a multilocular cystic lesion in the pancreatic tail after a routine ultrasound. Computed tomography and magnetic resonance cholangiopancreatography were performed, showing a multilocular cystic lesion with a hypervascular wall nodule in the pancreas. The patient underwent distal pancreatectomy, with a final diagnosis of pancreatic mucinous cystadenoma with an associated component of clear cell renal cell carcinoma (collision tumor of the pancreas).